Matriarchs as Repositories of Social Knowledge in African Elephants - McComb, Karen; Moss, Cynthia; Durant, Sarah M.; Baker, Lucy; Sayialel, Soila (Science (American Association for the Advancement of Science), 2001)
Despite widespread interest in the evolution of social intelligence, little is known about how wild animals acquire and store information about social companions or whether individuals possessing enhanced social knowledge derive biological fitness benefits. Using playback experiments on African elephants (Loxodonta africana), we demonstrated that the possession of enhanced discriminatory abilities by the oldest individual in a group can influence the social knowledge of the group as a whole. These superior abilities for social discrimination may result in higher per capita reproductive success for female groups led by older individuals. Our findings imply that the removal of older, more experienced individuals, which are often targets for hunters because of their large size, could have serious consequences for endangered populations of advanced social mammals such as elephants and whales.